2002
DOI: 10.1034/j.1399-6576.2002.460209.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous anesthetics on interleukin (IL)‐6 and IL‐10 production by lipopolysaccharide‐stimulated mononuclear cells from healthy volunteers

Abstract: Propofol appears to inhibit both IL-6 and IL-10 production by LPS-stimulated PBMCs in vitro. Further study is required to clarify the mechanism of the suppressive effect of propofol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 13 publications
1
35
0
2
Order By: Relevance
“…Previous in vitro studies demonstrated conflicting results as to whether propofol exerts dose-related effects on endotoxemia [9,10], and in vivo studies are few. Our present study showed that only a medium dose of propofol inhibited an increase in the TNF-α concentration.…”
Section: Discussionmentioning
confidence: 98%
“…Previous in vitro studies demonstrated conflicting results as to whether propofol exerts dose-related effects on endotoxemia [9,10], and in vivo studies are few. Our present study showed that only a medium dose of propofol inhibited an increase in the TNF-α concentration.…”
Section: Discussionmentioning
confidence: 98%
“…Die Regulationsmechanismen, die Syntheseprozesse und Wirkorte dieser Stoffe in der Leber im Rahmen von Entzündungsreaktionen sind aber noch weit gehend unbekannt. [56]. Propofol hemmte schon in niedrigen Konzentrationen die Bildung von IL-6 (proinflammatorischer Mediator) und IL-0 (überwiegend antiinflammatorischer Mediator).…”
Section: Prostaglandineunclassified
“…Compared with group C, 60 min after SLV, never put off till tomorrow what you can obviously increase the SOD activity, and MDA concentration is reduced, that sevoflurane pre-treatment can reduce the generation of oxygen free radicals. And 30 min after SLV [4], group S MDA concentration higher than that of group C, the role of sevoflurane metabolism in the body could be produced in the process of oxidation to alkyl peroxide further to produce oxygen free radical, antioxidant mechanism of jump-starting the body, inhibition of oxygen free radicals generated in the end [5]. concentration to 0.…”
Section: Anaesthesia Methodsmentioning
confidence: 99%